Wasiat Wajibah Untuk Anak Angkat Menurut Imam Madzhab dan Hukum Positif di Indonesia - Misno Mohammad Djahri (JURNAL ALAMIAH, 2020)
Islamic law is a perfect legal system, it regulates all aspects of human life, from state issues to individual and family problems. In family matters, it has been regulated in detail regarding the distribution of inheritance, each family member who becomes the heir has determined its share. However, not all families are blessed with children, so some married couples take a child to be adopted as an adopted child. What is the position of adopted children in Islamic law? And does he get an inheritance from his adoptive parents? The syar'i texts sourced from the Qur'an and Sunnah are not found explicitly regarding inheritance for adopted children, but implicitly the spirit of Islam always protects every child who still needs protection and care. Therefore, Islamic jurists have formulated a mandatory will for adopted children. Mandatory wasat is a will that is determined by an imam (head of state) for the inheritance of someone who has adopted children who still need care. The amount of a mandatory will as a will in general is not more than 1/3 of the total inheritance. Some of the conditions related to the implementation of the mandatory will is that the adopted child still needs money for his daily needs.